Risk factors predicting need for the pediatric intensive care unit (PICU) post-hematopoietic cell transplant, PICU utilization, and outcomes following HCT: a single center retrospective analysis - Johnson, Amanda K.; Cornea, Sinziana; Goldfarb, Samuel; Cao, Qing; Heneghan, Julia A.; Gupta, Ashish O. (Frontiers in Pediatrics, 2024)
Hematopoietic cell transplant (HCT) is a curative treatment for multiple malignant and non-malignant disorders. While morbidity and mortality have decreased significantly over the years, some patients still require management in the pediatric intensive care unit (PICU) during their HCT course for additional respiratory, cardiovascular, and/or renal support. We retrospectively reviewed pediatric patients (0 to 18 years) who underwent HCT from January 2015 to December 2020 at our institution to determine risk factors for PICU care and evaluate PICU utilization and outcomes. We also assessed pulmonary function testing (PFT) data to determine if differences were noted between PICU and non-PICU patients as well as potential evolution of pulmonary dysfunction over time. Risk factors of needing PICU care were lower age, lower weight, having an underlying inborn error of metabolism, and receiving busulfan-based conditioning. Nearly half of PICU encounters involved use of each of respiratory support types including high-flow nasal cannula, non-invasive positive pressure ventilation, and mechanical ventilation. Approximately one-fifth of PICU encounters involved renal replacement therapy. Pulmonary function test results largely did not differ between PICU and non-PICU patients at any timepoint aside from individuals who required PICU care having lower DLCO scores at one-year post-HCT. Future directions include consideration of combining our data with other centers for a multi-center retrospective analysis with the goal of gathering and reporting additional multi-center data to work toward continuing to decrease morbidity and mortality for patients undergoing HCT.